179 Protective Effects of Soybean Isoflavones in Broilers Challenged with Infectious Bursal Disease Virus. (7th December 2018) - Jiang, S; Li, L; Fan, Q; Wang, Y; Gou, Z; Lin, X; Jiang, Z
Abstract: The experiment was conducted to investigate the effects of dietary supplementation with soybean isoflavones (SI) on growth performance, antioxidant and immune capacity in broilers infected with infectious bursal disease virus (IBDV). A total of 200 one-day-old male broilers were randomly assigned to five treatments. Each treatment consisted of four replicates with 10 birds per replicate. From one-day-old on, diets in IBDV+10SI group, IBDV+20SI group and IBDV+40SI group was supplemented with 10mg/kg, 20mg/kg and 40mg/kg soybean isoflavones in basal diet respectively, while diets in normal and IBDV groups were without soybean isoflavones supplementation. At 21 days of age, broilers were inoculated with 50 bursal infectious dose (BID) of the IBDV BC 6/85 strain by the eye-drop route except the normal group. Results showed that: After inoculated with IBDV, the growth performance of IBDV group decreased, 42-day-old BW, 22–42 ADG and 22–42 ADFI decreased by 4.70% ( P =0.0922), 6.80% ( P <0.05) and 5.57% ( P <0.05), respectively compared with the normal group. During this period, broilers in IBDV+20SI group had the best growth performance.Diets supplemented with 10mg/kg soybean isoflavones significantly increased the weight of the Bursa of Fabricius compared with IBDV group, and reduced the IBDV mRNA expression and NF-κB production in Bursa of Fabricius ( P <0.05). High dosage of soybean isoflavones (40mg/kg) had bursal IL-2 content increased significantly ( P <0.05). At day 3 post inoculation, broilers in IBDV group had the T-AOC, GSH-Px activity of serum and T-AOC, GSH-Px, SOD, CAT activity of jejunum mucosa decreased significantly compared to the normal group ( P <0.05). Diets supplemented with 10, 20, 40 mg/kg soybean isoflavones significantly improved the serum T-AOC of infected broilers ( P <0.05). It was concluded that diets supplemented with 20 mg/kg soybean isoflavones can improve antioxidant capacity and the resistance to IBDV infection in broilers and promote the recovery of infected broilers.